(untitled) (Revista de Investigaciones Universidad del Quindío, 2013)
Digital Elevation Models (DEM) are defined as numerical data structures that represent the spatial distribution of elevation above the surface. From the 70’s was established the representation of surfaces generated by the TIN model as the most appropriate, but by its nature, this algorithm follows a linear function, while the geometry of nature is showing a chaotic behavior, for that reason could achieve a better representation of these forms with the implementation of Kriging algorithm allowing to analyze the statistical variation over different distances and directions, causing the minimum error in estimated elevation; this work seeks to establish the relationship between surface geometry and the interpolation algorithm, through an analysis of variance (ANOVA) of Root Mean Square Error (RMSE) of a sample of 80 different models ranked according to their slope.